Effectiveness of learning human anatomy using three-dimensional augmented reality application; [Skuteczno nauki anatomii czowieka z wykorzystaniem aplikacji rzeczywistoci rozszerzonej w trjwymiarze] - Gunathevan a/l Elumalai, Fairus Fariza binti Zainudin, Nurul Fadhilah Binti Abdullah, Mohansundar Sankaravel, Fariba Hossein Abadi (Tanjung Malim, 2024)
Effectiveness of learning human anatomy using three-dimensional augmented reality application; [Skuteczno nauki anatomii czowieka z wykorzystaniem aplikacji rzeczywistoci rozszerzonej w trjwymiarze] by Gunathevan a/l Elumalai, Fairus Fariza binti Zainudin, Nurul Fadhilah Binti Abdullah, Mohansundar Sankaravel, Fariba Hossein Abadi